Dynamic performance enhancement of an electro-pneumatic clutch actuator using MATLAB-based modeling and advanced control strategies - Fysun, S.; Yarita, O.; Фисун, Станіслав Сергійович; Ярита, Олександр Олександрович (Харківський національний автомобільно-дорожній університет, 2026)
Electro-pneumatic clutch actuators used in automated transmission systems operate under nonlinear conditions and varying external loads, which complicates the design of stable and accurate control systems. Classical PID controllers often demonstrate limited robustness under actuator saturation and parameter variations. Goal. The purpose of this work is to improve the dynamic performance of an electro-pneumatic clutch actuator and to perform a comparative analysis of different control strategies under identical simulation conditions. Methodology. A simplified second-order dy-namic model of the electro-pneumatic actuator was developed in MATLAB. The model includes equiv-alent mass, damping, clutch spring stiffness, actuator saturation, velocity constraints, and external dis-turbance loading. Three control strategies were investigated: classical PID control, adaptive gain-scheduling control, and a simplified fuzzy-based nonlinear controller. Results. The obtained simulation results demonstrate that the adaptive controller provides the best overall dynamic performance in terms of settling time and tracking accuracy. The fuzzy-based controller ensures smoother transient behavior and reduced oscillatory response near the target position. Quantitative comparison of overshoot and RMS tracking error confirms the effectiveness of adaptive and nonlinear control approaches for electro-pneumatic clutch systems. Originality. The originality of the proposed approach lies in the development of a unified simulation framework that allows comparative evaluation of several control strategies un-der identical actuator constraints and disturbance conditions. Practical value. The developed simula-tion model and control approaches may be used for further optimization of automated clutch control systems in automotive transmission applications, particularly for improving shift quality, reducing me-chanical wear, and increasing actuator stability under varying operating conditions.
Покращення динамічних характеристик електропневматичного приводу зчеплення із використанням MATLAB-моделювання та сучасних стратегій керування
Keywords: electro-pneumatic actuator; clutch control; adaptive control; PID controller; fuzzy control; MATLAB; transmission systems; електропневматичний привід; керування зчепленням; адаптивне керування; ПІД-регулятор; нечітке керування; трансмісійні системи; 621.43.044: 681.5; 10.30977/AT.2219-8342.2026.58.0.04